Ketogal: A Derivative Ketorolac Molecule with Minor Ulcerogenic and Renal Toxicity - Russo, Roberto; De Caro, Carmen; Avallone, Bice; Magliocca, Salvatore; Nieddu, Maria; Boatto, Gianpiero; Troiano, Roberta; Cuomo, Rosario; Cirillo, Carla; Avagliano, Carmen; Cristiano, Claudia; La Rana, Giovanna; et al. (Frontiers in Pharmacology, 2017)
Ketorolac is a powerful non-steroidal anti-inflammatory drug (NSAID), with a great analgesic activity, present on the Italian market since 1991. Despite the excellent therapeutic activity, the chronic use of ketorolac has long been limited owing to the high incidence of gastrointestinal and kidney side events. In our previous study, we demonstrated that ketorolac-galactose conjugate ketogal, synthesized and tested in a single-dose study, was able to reduce ulcerogenicity, while preserving the high pharmacological efficacy of its parent drug. In this paper, in order to verify the suitability of this compound, for repeated administration , ex vivo experiments on naïve mice were performed. Mice were treated for 5 or 7 days with the highest doses of two drugs (ketorolac 10 mg/kg, ketogal 16.3 mg/kg), and the expression of both gastric COX-1 and PGsyn was evaluated. Results showed that oral ketorolac treatment, significantly reduced both enzymes; surprisingly, oral treatment with ketogal did not produce significant variation in the expression of the two constitutive enzymes. Moreover, histological experiments on stomach and kidneys clearly indicated that repeated administration of ketogal induced lower toxicity than ketorolac. At same time, in vivo results clearly showed that both ketorolac and ketogal had a similar therapeutic activity in a model of inflammation and in pain perception. This effects were accompanied by the reduction of enzyme expression such as COX2 and iNOS, and by the modulation of levels of nuclear NF-kB and cytosolic IkB-alpha in the inflamed paws. These very encouraging results demonstrate for the first time that ketogal could represent a valid and novel therapeutic alternative to the ketorolac and might pave the way for clinical studies. These very encouraging results demonstrate for the first time that ketogal could represent a valid and novel therapeutic alternative to the ketorolac and might pave the way for clinical studies.